Floating microspheres encapsulating carvedilol for the effective management of hypertension - Sapna Patel; Naina Dubey; Asmita Gajbhiye; Shailendra Patil (Mazandaran University of Medical Sciences, 2019)
Carvedilol (CVD) is an antihypertensive agent with a short half-life, pH-dependent solubility, and narrow absorption window. The purpose of this research was to prepare a floating-drug delivery-system of carvedilol to increase its half-life. The present study investigates the preparation of carvedilol-floating microspheres, evaluates the floating-drug delivery-system (FDDS) (by scanning electron microscope), it's in vitro stability, and in vivo profile. Floating microspheres were prepared by solvent-evaporation (oil-in-water emulsion) technique using hydroxypropyl methylcellulose (HPMC) and ethyl cellulose (EC) as the rate controlling polymers. The surface morphology of the prepared microspheres w:as char:acterized by scanning electron microscopy. In this study, the particle size analysis, drug entrapment efficiency, surface morphology, buoyancy percentage, and release studies were performed. The microspheres were found to be spherical and porous. The results showed that the mean/mean (SD) values of tapped density, Carr's compressibility index, angle of repose, percentage yield, in vitro buoyancy, %entrapment efficiency of CVD-loaded floating microspheres were 0.42 (0.012), 12.5 (1.895), 23.5 (1.856), 80.2 %, 79.0 %, and 85.81(1.40), respectively. The developed floating-microsphere of CVD released the drug for 24 h and based on in vivo studies, the drug-loaded floating microspheres help in maintaining the mean (SD) systolic blood pressure within the range of 120 (0.32) to 120 (1.02) mmHg and diastolic pressure within 91 (0.71) to 92 (0.79) mmHg. Thus, floating microsphere of CVD offers a suitable and practical approach for prolonged release of the drug over an extended period, and thus improves the oral bioavailability and efficacy of the drug as well as the patient's compliance.